The Courtauld News (The Courtauld Institute of Art, London). (Londen : Courtauld Institute of Art, University of London.)
The Courtauld News is an annual publication sent out to all alumni, students, staff and supporters of The Courtauld.(https://courtauld.ac.uk/alumni/courtauld-news)
Online: https://courtauld.ac.uk/alumni/courtauld-news
Engels
Tijdschriften
Keywords: The Courtauld Institute of Art (Londen).